2022
DOI: 10.1177/09637214221078592
|View full text |Cite
|
Sign up to set email alerts
|

Gender Prototypes Shape Perceptions of and Responses to Sexual Harassment

Abstract: We provide a model describing how the narrow prototype of women as having conventionally feminine attributes and identities serves as a barrier to perceiving sexual harassment and appropriately responding to sexual-harassment claims when the victims of harassment do not resemble this prototype. We review research documenting that this narrow prototype of women overlaps with mental representations of sexual-harassment targets. The prototype of women harms women who diverge from this prototype: Their experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…There are two approaches to prototype fit: within-group prototypicality, which refers to variation within a group on traits, interests, and behaviors that are prototypical of that group, and between-group prototypicality, which refers to variation between intersectional groups who possess two or more subordinate social identities. More specifically, a prototypical woman is stereotypically feminine rather than masculine in her traits, interests, and behaviors (within-group prototypicality), and White rather than Black, in her intersectional identities (between-group prototypicality) [24]. In a meta-analysis of four studies, a sexual harassment target's within-group prototypicality significantly impacted bystander intervention where bystanders had a greater threshold for intervention in a stereotypically masculine (nonprototypical) vs feminine (prototypical) woman's harassment [25].…”
Section: Prototypes Shape Relative Neglect In Bystander Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two approaches to prototype fit: within-group prototypicality, which refers to variation within a group on traits, interests, and behaviors that are prototypical of that group, and between-group prototypicality, which refers to variation between intersectional groups who possess two or more subordinate social identities. More specifically, a prototypical woman is stereotypically feminine rather than masculine in her traits, interests, and behaviors (within-group prototypicality), and White rather than Black, in her intersectional identities (between-group prototypicality) [24]. In a meta-analysis of four studies, a sexual harassment target's within-group prototypicality significantly impacted bystander intervention where bystanders had a greater threshold for intervention in a stereotypically masculine (nonprototypical) vs feminine (prototypical) woman's harassment [25].…”
Section: Prototypes Shape Relative Neglect In Bystander Interventionmentioning
confidence: 99%
“…For example, sexual harassment is often framed as discrimination based on gender alone, neglecting Black women's unique experiences with sexual harassment based on their race and gender [21,28]. Indeed, stereotypical attributes of the category "victim of gender discrimination", overlap more so with stereotypical attributes of White vs Black women, and Black women are perceived as less likely targets of sexual harassment than White women [24,29,30].…”
Section: The Costs Of Nonprototypicality For Black Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we investigate whether WHR is part of sexual victimization prototypes. Past work suggests that the prototypic individual who has been sexually victimized is a feminine and attractive White woman who fought back against the perpetrator and is emotional about her victimization (e.g., Kaiser et al, 2022; McKimmie et al, 2014; Schuller et al, 2010). Given that WHR is a sexually dimorphic trait that influences judgments of attractiveness, we hypothesize that WHR may affect whether women are perceived as aligned or misaligned with this prototype.…”
Section: Dimensions Of Sexual Perception: Unrestrictedness and Victim...mentioning
confidence: 99%
“…Importantly, there is evidence that cues of prototypicality can have important downstream effects in judgments of sexual victimization reports (see Kaiser et al, 2022 for review of gender prototypes and responses to sexual harassment). For example, Schuller and colleagues (2010) found that participants believed a woman’s sexual victimization report less if she was portrayed as behaving in non-gender stereotypic ways.…”
Section: Dimensions Of Sexual Perception: Unrestrictedness and Victim...mentioning
confidence: 99%